IMPLEMENTASI KARAGUL-SAHIN APPROXIMATION METHOD UNTUK MEMINIMALISASI BIAYA PENDISTRIBUSIAN AIR PADA MASALAH TRANSPORTASI - Basriati, Sri; Safitri, Elfira; Nusantoro, Dinda Kurniyawan (Math Educa Journal, 2021)
Transportation problems such as transportation activities and allocation to reach consumers is one of the factors that determine the level of satisfaction. To find the level of customer satisfaction, it requires an appropriate and efficient transportation model. One of which is in the Air Minum Mata Air Sikumbang business owned by Mr. Zulfikar, located in Rumbio, Kampar. Based on the results of the study the cost of distributing drinking water is still not efficient because it still uses estimation and there is no separate technique used to allocate water distribution. The solution made in this study using the Karagul-Sahin Approximation Method for the initial basic feasible solution and Stepping Stone for the optimal solution value so as to obtain the distribution of water at a minimum cost. Based on research using the method of  Karagul-Sahin Approximation and Stepping Stone, a weekly cost savings of Rp.469.515,00 is obtained.